Digital Transformation and AI Implementation Effects on SME Financial Performance in Emerging Economies - Fatimah, Shela; Puspitasari, Diana (Inovasi Analisis Data, 2026)
Purpose: This paper examines the impact of digital transformation and AI capabilities on MSME financial performance in an emerging economy via operational efficiency. Method: A quantitative survey is used as a method of data collection for the study and PLS-SEM is used to test the mediation and moderation. Findings: Results show that digital transformation capability, AI usage intensity, IT infrastructure preparedness and TTMS' (i.e., top management teams) digital competency drive operational efficiency, which in turn enhances financial performance. No direct financial implications from using AI or digital transformation capability are identified, highlighting that technological value is mainly achieved through operational efficiencies. On the other hand, IT infrastructure preparedness and digital management competence demonstrate both a direct and an indirect effect on performance. Environmental uncertainty has no direct effects on financial performance and does not moderate the relationships under study, indicating that digital and AI capabilities serve as basic rather than contingent drivers in this setting. Novelty: This work adds by disambiguating the mediating role of digital value creation in MSME and by questioning the tacit boundary condition effect of environmental uncertainty in emerging economy context. Implications: The findings emphasize therefore the necessity for integrating digital and AI strategy at heart of business process and developing managerial digital competencies to achieve durable performance improvements.